(untitled) (GEOmedia, 2023)
PASSport is an Operational Platform managing a fleet of semi-autonomous drones exploiting GNSS High Accuracy and Authentication to improve Security & Safety in port areas. EUSPA funded the project that responds to the needs expressed by port authorities, harbour master and border control authorities by extending situational awareness to improve safety and security in port areas.